Dualisation of part-time work: the development of labour market insiders and outsiders (Bristol, 2019)
"This book brings together leading international authors from a number of fields to provide an up-to-date understanding of part-time work at national, sector, industry and workplace levels. The contributors critically examine part-time employment in different institutional settings across Europe, the USA, Australia and Korea. This analysis serves as a prism to investigate wider trends, particularly in female employment, including the continued increase in part-time work and processes that are increasingly creating dualisation and inequality between ‘good’ and ‘bad’ jobs."